Crack-free GaN substrates grown by the Na-flux method with a sapphire dissolution technique. (24th June 2016) - Yamada, Takumi; Imanishi, Masayuki; Nakamura, Kosuke; Murakami, Kosuke; Imabayashi, Hiroki; Matsuo, Daisuke; Honjo, Masatomo; Maruyama, Mihoko; Imade, Mamoru; Yoshimura, Masashi; Mori, Yusuke
Abstract: GaN wafers are generally fabricated by separating a foreign substrate from a GaN layer using thermal stress; however, thermal stress also leads to the cracking of the GaN layer. In this study, we first succeeded in dissolving a sapphire substrate just after Na-flux growth by successively changing the flux content for GaN growth (Ga–Na–C) to that for dissolving sapphire (Ga–Na–C–Li) at the considered growth temperature. Hence, no thermal stress was induced in the grown GaN crystals, resulting in a crack-free GaN substrate. We concluded that this process is a good candidate technique for supplying free-standing GaN substrates.